Copper Ions Facilitate the Conjugative Transfer of SXT/R391 Integrative and Conjugative Element Across Bacterial Genera - Song, Zhou; Zuo, Lei; Li, Cui; Tian, Yiming; Wang, Hongning (Frontiers in Microbiology, 2021)
Copper can persist stably in the environment for prolonged periods. Except for inducing antibiotic resistance in bacteria, copper ions (Cu2+) can facilitate the horizontal transfer of plasmid DNA. However, whether and how Cu2+ can accelerate the conjugative transfer of SXT/R391 integrative and conjugative element (ICE) is still largely unknown. In this study, Proteus mirabilis ChSC1905, harboring an SXT/R391 ICE that carried 21 antibiotic resistance genes (ARGs), was used as a donor, and Escherichia coli EC600 was used as a recipient. Cu2+, at subinhibitory and environmentally relevant concentrations (1 μmol/L–10 μmol/L), significantly accelerated the conjugative transfer of SXT/R391 ICE across bacterial genera (from P. mirabilis to E. coli) (p < 0.05). The combined analyses of phenotypic tests and genome-wide sequencing indicated that reactive oxygen species production and cell membrane permeability were critical in the enhanced conjugative transfer of SXT/R391 ICE. Furthermore, the expression of genes related to cell adhesion and ATP synthesis was also significantly upregulated on exposure to Cu2+ at a concentration of 5 μmol/L. This study clarified the potential mechanisms of Cu2+ to promote the conjugative transfer of SXT/R391 ICE, revealing the potential risk imposed by Cu2+ on the horizontal transfer of SXT/R391 ICE-mediated ARGs.